2016
DOI: 10.1080/13527266.2016.1138138
|View full text |Cite
|
Sign up to set email alerts
|

Why should I believe this? Deciphering the qualities of a credible online customer review

Abstract: His research interests are concerned with the use and influence of electronic word-of-mouth on customer attitudes and decisions, and the use of CAQDAS to facilitate qualitative data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…Thomas et al (2019) found that argument quality, related to argument strength, is the primary factor affecting review credibility. Other research has proven that strong arguments serve as a significant predictor of the perceived usefulness of the review (Clare et al, 2018;Filieri et al, 2018a). For instance, Wang and Li (2019) found that information quality, also related to argument strength, is positively associated with the perceived usefulness of review websites.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thomas et al (2019) found that argument quality, related to argument strength, is the primary factor affecting review credibility. Other research has proven that strong arguments serve as a significant predictor of the perceived usefulness of the review (Clare et al, 2018;Filieri et al, 2018a). For instance, Wang and Li (2019) found that information quality, also related to argument strength, is positively associated with the perceived usefulness of review websites.…”
Section: Literature Reviewmentioning
confidence: 99%
“…WOM is defined as direct communication from person-to-person of an opinion about a product and/or service [18]. The diffusion of WOM is an important mechanism for information to reach a large population, thereby possibly influencing 1) public opinion; 2) adoption of innovation; and 3) the market share of a new product or brand awareness [19].…”
Section: E-wommentioning
confidence: 99%
“…According to the ELM [31], involvement in the processing of information through the central route or the peripheral route refers to personal relevance or importance of a product or service [43]. Even tough in the original ELM model is consider to have a moderating effect [35], [36], [60], [61]. Based on the work developed by Schlesinger and Güngerich (2011) [60] in which they relate product involvement with the credibility of these product for sponsorship effectiveness.…”
Section: B Hypotheses Developmentmentioning
confidence: 99%